Type 3 innate lymphoid cell-derived lymphotoxin prevents microbiota-dependent inflammation. Issue 7 (July 2018) - Zhang, Yuan; Kim, Tae-Jin; Wroblewska, Joanna A; Tesic, Vera; Upadhyay, Vaibhav; Weichselbaum, Ralph R; Tumanov, Alexei V; Tang, Hong; Guo, Xiaohuan; Tang, Haidong; Fu, Yang-Xin
Abstract Splenomegaly is a well-known phenomenon typically associated with inflammation. However, the underlying cause of this phenotype has not been well characterized. Furthermore, the splenomegaly phenotype seen in lymphotoxin (LT) signaling-deficient mice is characterized by increased numbers of splenocytes and splenic neutrophils. Splenomegaly, as well as the related phenotype of increased lymphocyte counts in non-lymphoid tissues, is thought to result from the absence of secondary lymphoid tissues in LT-deficient mice. We now present evidence that mice deficient in LTα1 β2 or LTβR develop splenomegaly and increased numbers of lymphocytes in non-lymphoid tissues in a microbiota-dependent manner. Antibiotic administration to LTα1 β2 - or LTβR-deficient mice reduces splenomegaly. Furthermore, re-derived germ-freeLtbr −/− mice do not exhibit splenomegaly or increased inflammation in non-lymphoid tissues compared to specific pathogen-freeLtbr −/− mice. By using various LTβ- and LTβR-conditional knockout mice, we demonstrate that retinoic acid-related orphan receptor γT-positive type 3 innate lymphoid cells provide the required active LT signaling to prevent the development of splenomegaly. Thus, this study demonstrates the importance of LT-mediated immune responses for the prevention of splenomegaly and systemic inflammation induced by microbiota.